Pengaruh Harga, Online Customer Rating, Online Customer Review, Dan E-Service Quality Pada Keputusan Pembelian Pada E-Commerce Shopee (Studi Pada Mahasiswa Universitas Islam Malang) - Khoyyimah, Khoyyimah; Rachma, N; Ramadhan, Tri Sugiarti (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study is to understand how price, online customer reviews, online customer ratings, and e-service quality affect consumers' decisions to buy from Shopee (a study conducted among Universitas Islam Malang students). There are about 115 samples that are used using the Malhotra rumus. Data is obtained by using the purposive sample technique to interview students at Universitas Islam Malang. Uji validitas, uji reliabilitas, uji normalitas, uji asumsi klasik, uji analisis regresi linear berganda, uji f, uji t, and uji koefisien determinasi (R2) are among the data analysis tools used in this study. The study's findings indicate that, all at once, price, online customer reviews, online customer ratings, and e-service quality have a positive and significant impact on buyers' decisions. Additionally, each independent variable has a parsimal impact on the dependent variable. Keywords : Price, Online Customer Rating, Online Customer Review, E-Service Quality dan Purchasing Decision.